COMPETENCE, ORGANIZATIONAL CULTURE, WORK TEAM TO HUMAN CAPITAL RESOURCES MANAGEMENT DIRECTORATE - Rr. Lulus Prapti; Adhi Widyakto; Edy Suryawardana (JURNAL STUDI MANAJEMEN ORGANISASI, 2021)
This research about the human capital approach to manage human resources becoming  productive. The method used is qualitative method with descriptive research. Human capital approach for the implementation has five maain components, i.e individual capability, individual motivation, the organization climate, workgroup effectiveness and leadership. Recognizing the importance of human resource company activities, needed to optimal manage human resources because the key to success  a company isn’t only benefits of technology and availability of funds, but also on the human factor. Based on observations in Indonesia, there are still many companies doesn’t have  implemented the most optimal approach to human capital. The results of  study indicate that the human capital component  hasn’t been optimal, especially in terms of individual capability and individual motivationThe purpose of  study was determine the effect of several variables such as competence, leadership, and work discipline on employeess performance. The method used is descriptive and causality. The statistical test in this study uses Multiple Regression Analysis. Respondents involved in this study were 93 employeess who were permanent employeess at the Human Resources and Facility Management Directorate at PT Telekomunication Indonesia, Jakarta Head Office. The sampling method of his research  using purposive sampling. Data accumulation techniques using questionnaires and interviews. Data analysis was performed using multiple regression. The results indicates that partially competence has an effect on employeess performance, The Orgamizatation Climte doesn’t affect employees performance, work Group Efficiency affects employees performance.